Post-COVID-19 fatigue and health-related quality of life in Saudi Arabia: a population-based study - Al-Johani, Moath S.; Khalil, Rehana; Al-Mohaimeed, Yazeed A.; Al-Mundarij, Omar M.; Al-Samani, Abdulmajeed S.; Al-saqry, Osama S.; Al-saawi, Alwaleed A.; Al-dhali, Ibrahim K.; Al-Essa, Waleed A. (Frontiers in Public Health, 2023)
Background Despite substantial literature on symptoms and long-term health implications associated with COVID-19; prevalence and determinants of post-acute COVID-19 fatigue (PCF) remain largely elusive and understudied, with scant research documenting health-related quality of life (HRQoL). Hence, prevalence of PCF and its associated factors, and HRQoL among those who have survived Covid-19 within the general population of Saudi Arabia (KSA) is the subject under examination in this research. Methods This cross-sectional study was conducted on 2063 individuals, selected from the KSA’s general population, using a non-probability sampling approach. An online survey was used to employ a self-administered questionnaire to the participants, which included socio-demographic information, the patient’s COVID-19 infection history, 12-item Short Form Health Survey (SF-12) to assess quality of life, and Chalder Fatigue Scale (CFS) (CFQ 11) to evaluate the extent and severity of fatigue. Data were analyzed using SPSS version 26. A p < 0.05 was considered to be strong evidence against the null hypothesis. Results The median age of participants was 34 (IQR = 22) years, with females comprising the majority (66.2%). According to the SF-12 questionnaire, 91.2% of patients experienced physical conditions, and 77% experienced depression. The prevalence of PCF was 52% on CFQ 11 scale. Female gender, higher levels of education, a pre-existing history of chronic disease, as well as the manifestations of shortness of breath and confusion during acute COVID-19 infection, were identified as independent predictors of fatigue. Conclusion To facilitate timely and effective intervention for post-acute COVID-19 fatigue, it is essential to continuously monitor the individuals who have recovered from acute COVID-19 infection. Also, it is critical to raise health-education among these patients to improve their quality of life. Future research is required to determine whether COVID-19 survivors would experience fatigue for an extended duration and the impact of existing interventions on its prevalence and severity.